2000
DOI: 10.1021/ol006766l
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Benzyloxyaniline Linker Utilizing Ceric Ammonium Nitrate (CAN) as a Cleavage Reagent:  Solid-Phase Synthesis of N-Unsubstituted β-Lactams and Secondary Amides

Abstract: [figure: see text] A novel benzyloxyaniline linker that uses ceric ammonium nitrate (CAN) as a cleavage reagent is described. Its application in the solid-phase synthesis of N-unsubstituted beta-lactams and secondary amides furnishes compounds in moderate to excellent yield (45-91%) and high purity (93-99%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…For example, the acylation of Rink amide secondary amines with amino acids possessing bulky side chains was reported to occur in only modest yields (60%) [95]. The authors have reported a new amine linker of this category that is cleaved using ceric [96] ammonium nitrate [Ce(NO 3 ) 6 (NH 4 ) 2 , CAN]. The linker has been designed for the release of secondary amides and, in particular, b-lactams but will have broader application.…”
Section: Solid-phase Techniques For B-lactam Synthesismentioning
confidence: 99%
“…For example, the acylation of Rink amide secondary amines with amino acids possessing bulky side chains was reported to occur in only modest yields (60%) [95]. The authors have reported a new amine linker of this category that is cleaved using ceric [96] ammonium nitrate [Ce(NO 3 ) 6 (NH 4 ) 2 , CAN]. The linker has been designed for the release of secondary amides and, in particular, b-lactams but will have broader application.…”
Section: Solid-phase Techniques For B-lactam Synthesismentioning
confidence: 99%
“…The most challenging of these reactions proved to be the Sn(II) reduction, which has been somewhat variable for the reduction of nitroaromatic molecules on solid phase by a number of groups pursuing other targets. An alternative approach would be to directly load an N-Boc protected 3-iodo-4-aminophenol [Gordon and Balasubramanian, 2001], which would circumvent the need for reduction of the nitro group on solid phase.…”
Section: Intramolecular Heck Reactionmentioning
confidence: 99%
“…CAN has been widely used in organic reactions which include oxidation, [12][13][14][15][16] oxidative addition, [17][18][19][20][21] photooxidation, 22 nitration, [23][24][25] deprotection, 26,27 graft polymerization, 28,29 etc. Intermediates formed in these reactions may undergo oxidative fragmentation, 30,31 rearrangement, [32][33][34] or C-H, C-C and C-S bond [35][36][37][38] cleavages. Organic sulfides can be oxidized with catalytic amounts of Ce(IV) salts rapidly and selectively to sulfoxides.…”
Section: Introductionmentioning
confidence: 99%